SPHENOID BONE LIGAMENTS’ ENTHESOPATHY WITH THEIR CLINICAL MANIFESTATIONS - SUMITA AGARWAL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The Cortical bone formation at enthesial sites of ligament attachments to the sphenoid bone is indeed multifactorial, involving various biological, mechanical, and biomechanical processes. The present study is aimed to observe the ossified ligaments of sphenoid bone of skull manifesting various neurological complications. Methods: An observational study conducted on sphenoid bones of 36 dried human skulls of unknown gender and age procured from the Department of Anatomy at Gautam Buddha Chikitsa Mahavidyalaya, Dehradun and People’s College of Medical Sciences and Research Centre, Bhopal. These bones were observed for enthesopathic modifications in their ligaments. Results: The present study showed ossified caroticoclinoid ligament (intra cranial ligament) predominated by 41.66% followed by pterygospinous ligament ossification (extra cranial ligament) with total 38.88% prevalence. Conclusion: Altered morphology of sphenoid bone knowledge is a must for neurosurgeons and orthopedic surgeons while operating at these sites to avoid hindrances and has scope for newer approaches for better prognosis.